ʿUrf Patrilocal Residence Patterns from the Perspective of Islamic Family Psychology - Mohammed Hafiz Ali Wafa; Nurul Latifah; Nashih Muhammad (Yayasan Azhar Amanaa Yogyakarta, 2025)
The background of this study is the conflict that occurs in patrilocal families in Gentingsari Village. In patrilocal families, the implementation of family functions is disrupted due to the presence of in-laws living in the same house. The disrupted of family functions can cause conflicts between husband and wife as with in-laws. If conflicts in patrilocal families cannot be resolved completely, it can hinder the achievement of a harmonious family. The objectives of this study are to determine how family functions are implemented in patrilocal families in Gentingsari Village. The second objectives is to determine how conflicts that arise in patrilocal families in Gentingsari Village are resolved according to the perspective of Islamic family psychology. This research is classified as field research using a psychological approach. In collecting data, researchers used observation, interviews, and documentation methods. After the data was collected, the researcher summarized and sorted the data to be presented and analyzed. From the results of the research, it can be concluded that the implementation of family functions in patrilocal families in Gentingsari Village faces obstacles due to the involvement of external parties (in-laws). This causes problems between husbands and wives as well as with in-laws who live in the same house. Conflicts that arise in patrilocal families in Gentingsari Village are resolved by calming down before discussing the most appropriate solution. In addition, husbands and wives also apply constructive conflict resolution methods by understanding and comprehending the conflict so that it does not become more complicated